Prevalence and Preventive Measures of Infertility in Male by Kruger’s Criteria, a Randomized Study in Private and Government Health Care Hospitals (Bangladesh Journal of Medical Science, 2018)
Background: Every single couple out of 10 is in search of medical care because of infertility. Men older than 40 years and Women older than 30 years are at an increased risk of infertility. On the other hand, the estimation of male infertility is frequently underestimated or delayed. Symptomatic approaches steadily reducing the magnitude of couples classified as having idiopathic infertility. This is than perceived that no simple tests can conclude the probability of pregnancy in congregation in which the man is an infertile partner.Method: Current study is design to figure out existence, problems, and causes, associated with infertility and treatment. In the view of the fact that the investigative consequences responsible for infertility in male. For this purpose survey has been conducted at different private and government health care hospital (n=33 patient of infertility) were selected for further studies.Result: Results revealed that most of the patients are in the middle of their ages reported infertile. Primary infertility in infertile patients is 73% where as the presence of secondary infertility in the remaining respondent is 27%. Among all, 52% of the patients have co-morbid history of diabetes mellitus, 18% of them have issues about genitourinary trauma and infections, 30 patient have been identified problems related morphological count, 51% of them investigated abnormal volume of man semen. Evaluation of the study on infertility by Kruger’s strict morphology test over 75% of the men having insignificant infertility issues whereas 25% of them were observed significant infertility issues.Conclusion: It is concluded that male infertility is independent on the age factor according to our survey based study whereas, excessive use of tobacco, alcohol, high fat food consumptions, obesity, heavy weight exercises, sedative life styles, contacts with chemical or toxins, stress or psychological disturbances might provoke issues of infertility.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.94-99